2011
DOI: 10.1590/s0103-05822011000300006
|View full text |Cite
|
Sign up to set email alerts
|

Abordagem diagnóstica e terapêutica da toxoplasmose em gestantes e as repercussões no recém-nascido

Abstract: OBJETIVO:Avaliar a abordagem diagnóstica e terapêutica da toxoplasmose de gestantes que apresentaram IgM positiva para a doença e o acompanhamento de seus filhos em um hospital público no Rio de Janeiro, RJ. MÉTODOS: Estudo transversal retrospectivo de 2003 a 2006, realizado por meio da análise dos prontuários de 98 gestantes com sorologia IgM positiva para toxoplasmose e seus filhos (99 crianças). O seguimento das crianças com e sem infecção congênita foram analisados, assim como a apresentação clínica daquel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
3
13
0
13
Order By: Relevance
“…[4] Additionally, several studies conducted in Brazil have found seroprevalence rates varying from 42% to 90%. [18] Conversely Tekkesin (2012) reported that, although congenital toxoplasmosis is not a nationally reportable disease, extrapolation from regional studies indicates that an estimated 400: 4,000 cases occur in the United States each year. [3] Additionally, in Australia, primary infection with toxoplasmosis during pregnancy is rare.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[4] Additionally, several studies conducted in Brazil have found seroprevalence rates varying from 42% to 90%. [18] Conversely Tekkesin (2012) reported that, although congenital toxoplasmosis is not a nationally reportable disease, extrapolation from regional studies indicates that an estimated 400: 4,000 cases occur in the United States each year. [3] Additionally, in Australia, primary infection with toxoplasmosis during pregnancy is rare.…”
Section: Discussionmentioning
confidence: 99%
“…[18] The rate of fetal transmission of T. gondii parasite during frist infection is 60% to 65% in the third trimester, while the incidence of severe fetal infection falls from 75% to a negligible risk in late pregnancy, 30% to 54% in the second and 10% to 25% in the first trimester. [13,44] The highest mean knowledge score observed among pregnant women in the first trimester in pre-test (25.9 ± 14.2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations